High-performing rechargeable/flexible zinc-air batteries by coordinated hierarchical Bi-metallic electrocatalyst and heterostructure anion exchange membrane. (November 2019) - Xu, Nengneng; Zhang, Yanxing; Wang, Min; Fan, Xiujun; Zhang, Tao; Peng, Luwei; Zhou, Xiao-Dong; Qiao, Jinli
Abstract: Due to the lack of highly efficient and low-cost oxygen reduction reaction/oxygen evolution reaction (ORR/OER) catalyst and alkaline anion exchange membrane (AEM), advanced rechargeable zinc-air batteries are largely hindered in many applications from wearable electronics to electric vehicles. Herein, a hybrid of porous Co3 O4 anchoring on MnO2, then interpenetrating with CNTs (Co3 O4 /MnO2 -CNTs) is synthesized via facile hydrothermal process, and an AEM (CS/EMImC-Co-EP/GO) employing semi-interpenetrating network structure is fabricated with a simple solution-casting method. The porous nanoparticles and chrysalis-like hybrid as well as strong bi-metallic coupling effect build highways and buffer zones for reactant and electrons transfer for ORR/OER. In addition, due to the competition of bottom Co atoms, the density functional theory (DFT) proves that the neighbor Mn sites (Mn1 and Mn2) of the MnO2 (110) surface are evidently activated, which prompts the catalytic activity of hybrids by making the Mn1, Mn2 3d density of states move forward lower energy entirely. As a result, Co3 O4 /MnO2 -CNTs exhibit superior ORR/OER activities with the low potential difference (ΔE) of 0.85 V and impressive performances in rechargeable aqueous zinc-air batteries (power density: 534 mW cm −2 ). Moreover, combining AEM integrated into rechargeable flexible all-solid-state zinc-air batteries and stack, the enhancement natures of wearable devices are achieved even under different bending angles benefiting from high hydroxyl anion conductivity and remarkable flexibility of AEM semi-interpenetrating network, which accelerates ion transport by the synergy of hopping and vehicle mechanisms. Furthermore, the flexible all-solid-state zinc-air batteries show excellent tolerance toxicity of CO2 . Graphical abstract: A high-performing flexible all-solid-state Zn-air battery is achieved by coordinated hierarchical chrysalis-like Co/Mn electrocatalyst and heterostructure GO-enhanced anion exchange membrane.Image 1 Highlights: Co/Mn double oxide intertwined CNTs bifunctional chrysalis-like air cathodes have been developed. The single Zn-air cell delivers a discharge peak power density over 500 mW/cm 2, four times that using Pt/C. The 3-cell Zn-air stack represents an advanced level consistency of each cell, which has not been reported previously. °°°°°°The flexible batteries show strong durability to CO2 penetration due to the use of flexible anion-exchange membranes. DFT proves that MnO2 (110) surface are activated, making Mn1, Mn2 3d density of states move forward lower energy.